The study of carboxylic acids in flowers and leaves of Veronica chamaedrys L. and Veronica teucrium L. - Kovaleva, Аlla; Ilina, Тetyana; Raal, Ain; Osmachko, Alina; Goryacha, Olga; Rozhkovskyi, Yaroslav (ScienceRise: Pharmaceutical Science, 2020)
The aim. The genus Veronica (Veronica L.), family Plantaginaceae Juss. in the flora of Ukraine is represented by 64 species; Veronica chamaedrys L. and Veronica teucrium L. are widespread in the Kharkiv region. Plants are used in folk medicine as expectorants, anti-inflammatory, diaphoretic, anti-allergic, choleretic, antispasmodic, anticonvulsant, diuretic, sedative, wound healing and antibacterial agents. The aim of this work was to study the carboxylic acids of flowers and leaves of Veronica chamaedrys L. and flowers and leaves of Veronica teucrium L. Materials and methods. The objects of the study were flowers and leaves of Veronica chamaedrys L. and Veronica teucrium L., harvested in the flowering phase in 2018 in Kharkiv region, Ukraine. The study of carboxylic acids was performed by chromatography-mass spectrometry on a 6890N MSD/DS Agilent Technologies chromatograph with a 5973N mass spectrometric detector. Identification of acid methyl esters was performed using data from the mass spectrum library NIST 05 and Willey 2007 in combination with programs for the identification of AMDIS and NIST; also compared the retention time with the retention time of standard compounds. Results. In the flowers and leaves of Veronica teucrium L. 35 carboxylic acids were identified, the total content of which is 5.55 % and 2.93 %, respectively. 31 and 32 carboxylic acids were identified in the flowers and leaves of Veronica chamaedrys L., their total content is 5.39 % and 7.45 %, respectively. Conclusions. It is established that the flowers and leaves of Veronica chamaedrys L. are characterized by a higher content of carboxylic acids compared to the flowers and leaves of Veronica teucrium L. As chemotaxonomic markers of flowers and leaves the following compounds can be used: α-furanic acid for Veronica chamaedrys L.; veratric, 4-hydroxybenzylacetic and syringic acids for Veronica teucrium L. The obtained results will be the basis for further chemotaxonomic studies